Factors that influence occurrence of the endangered Asian tapir (Tapirus indicus desmarest) across forest reserves in Selangor and Negeri Sembilan, Malaysia - Durit, Samantha Liza anak (2019)
Asian tapir, Tapirus indicus is an endemic large mammal to Southeast Asia, whereby their population is declining due to deforestation. It is currently classified as endangered under IUCN with less than 2,500 mature individuals remaining. Deforestation is one of the main cause for biodiversity loss especially mammalian species, including large-sized like tapir. Deforestation can lead to a direct loss of wildlife habitat as well as overall degradation of their habitat. To assess their occurrence, camera-trapping method was used to gather data in eight forest reserves in the states of Selangor and Negeri Sembilan. Out of 345 cameratrapping locations, T. indicus was detected at 39 camera-trapping locations, represented by 960 images. Assessment of vegetation structure and landscape variables was carried out to identify the key drivers that may influence the presence of tapir. Corrected AIC (AICC) was used to compare the models and the best model (lowest value of AICC=2433) was selected, explained 61.70% of variation in tapir occurrence tallied to best subsets with 11 variables. These data highlight the importance of conserving the remaining fragmented forests. It was found out that tapir occurrence significantly increased with the number of trees with DBH 5 cm - 45 cm, number of saplings, proximity to road, altitude, trees with DBH more than 45 cm, but decreased with number of dead fallen trees, number of palms as well as the percentage of canopy cover. The findings from this study provide useful information for tapir conservation planning in fragmented forest landscapes. Safeguarding the ecological integrity of forest reserves and maintaining landscape connectivity among them are critically important for the conservation of T. indicus, but these measures are limited in highly fragmented forestry landscapes, interspersed with urban and agricultural matrices. Conserving the isolated tapir populations in fragmented landscapes may require direct intervention approaches such as reintroduction and restocking that can be costly and must be backed up by strong political will.